Preconception health beliefs and intentions predict behaviours among expectant male partners: a cross-sectional study - Tristan Carter; Danielle Schoenaker; Kris Rogers; Jon Adams; Amie Steel (Archives of Public Health)
Abstract Background The preconception period allows couples to plan and prepare for pregnancy. However, males can often consider this integral public health topic as a female domain. To better understand and support behaviour change for males before conception, this study aimed to identify and explore the preconception and pregnancy planning health beliefs and intentions of expectant male reproductive partners of pregnant women in Australia. Methods An online cross-sectional survey [2020–2021] among males aged 18–49 years who were the reproductive partner (expectant partner) of a pregnant female. Recruitment occurred via social media. The 80-item survey consisted of five sections. Survey items regarding beliefs and intentions were formulated using the Theory of Planned Behaviour. Associations between participants’ beliefs, subjective norms, perceived behavioural control, and intentions related to three outcomes (regular exercise, healthy diet, and alcohol avoidance) were estimated using Structural Equation Modelling. Results Expectant partners’ (n = 136) had a mean age of 31 years. Their beliefs toward regular exercise and their perceived behavioural control to exercise regularly were associated with a greater intention to exercise regularly (Standardised estimate β = 0.54; p = 0.0087 and β = 0.43; p = 0.02, respectively). The beliefs of expectant partners toward alcohol avoidance and their perceived behavioural control toward alcohol avoidance were associated with a greater intention to avoid alcohol (β = 0.43; p < 0.001 and β = 0.36; p < 0.001, respectively). For the healthy diet outcome, subjective norms of expectant partners, and perceived behavioural control to adopt a healthy diet were associated with an intention to adopt a healthy diet (β = 0.23; p = 0.04 and β = 0.47; p < 0.001, respectively). Intention was in turn associated with behaviour for all three outcomes. Conclusion Our study demonstrated that the preconception intentions of expectant partners were associated with their preconception behaviours; especially for the intention to exercise regularly or to avoid alcohol. Further studies examining paternal preconception health beliefs, and intentions and the motivations behind health behaviours for males are needed to help develop targeted preconception health promotion messages and interventions that support males to optimise their preconception health.